Finite element analysis with experimental validation of crack initiation in valve housing. (2020) - Nagendharan, S.; Kishore, R.; Gurusamy, P.; Subash, P.
Abstract: The paper reports that the study on crack analysis of valve housing, manufactured by cold forging process. It is reported that during the cold forging, frequent undue cracks are observed on the outer edges of the component. A detailed study was undertaken to analyses the micro structural defects in the forging process of a specimen. Scanning Electron Microscope (SEM) is performed on the component to understand its physical and chemical properties. To overcome the defects, the material geometry, and manufacturing process were optimized considering different constraints such as, manufacturing feasibility and cost. The computational modeling used to analyze the finite element analysis and optimize techniques. Also, the surface irregularities present on the die material, due to manual machining process is suggested to be rectified with the help of high accuracy automated machining centers. Results shows that the aforementioned defects occurred in the valve housing are completely eliminated and the material properties are enhanced for the expected life during end application.